Travel Umroh dalam Pengembangan Peradaban Islam di Kota Medan - Muktaruddin, Muktaruddin; Syahira, Jihan; Sukma, Tegar Arbia; Idris, Idris; Rafiqi, Muhammad (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Umrah travel is a container that can make it easier for Muslims to go to the baitullah, in the city of Medan itself Umrah travel already has so many agencies, with various kinds of price offers. In line with the development of the business and business world in Indonesia, the development of the Umrah and Hajj services sector is also very well developed, due to the fact that the waiting lines for performing the Hajj have been for more than 10 years. The analysis of Umrah travel is reviewed against the large number of pilgrims and the enthusiasm of the Muslims to participate. The relationship between Umrah travel and the development of Islamic civilization has the same path. Keeping up with the times, the current travel promotion system relies on information media, so that all the latest news is quickly conveyed to pilgrims or prospective pilgrims. Keywords: travel, umroh, development, Islam, civilization.